Campylobacter jejuni from Slaughter Age Broiler Chickens: Genetic Characterization, Virulence, and Antimicrobial Resistance Genes - Tsepo Ramatla; Kealeboga Mileng; Rendani Ndou; Mpho Tawana; Lehlohonolo Mofokeng; Michelo Syakalima; Kgaugelo E. Lekota; Oriel Thekisoe (International Journal of Microbiology)
Campylobacter jejuni is a major cause of food-borne human gastroenteritis worldwide and is designated as a high priority antimicrobial-resistant pathogen by the World Health Organization (WHO). In this study, a total of 26 C. jejuni isolates from broiler chickens were screened for the presence of virulence and antimicrobial resistance genes by PCR. As a result, the study detected 11/26 (42.3%), 9/26 (34.6%), 8/26 (30.8%), 7/26 (26.9%), 6/26 (23.1%), and 6/26 (23.1%) of cdtC, pldA, cdtB, cdtA, cadF, and ciaB virulence genes, respectively, with seven of the isolates carrying more than two virulence genes. The majority of the isolates n = 25 (96.1%) were resistant to nalidixic acid, followed by n = 21 (80.7%), n = 22 (84.6%), and n = 5 (19.2%) for tetracycline, erythromycin, and ciprofloxacin, respectively. Most isolates were harboring catI (n = 16; 84.2%), catII (n = 15; 78.9%), catIII (n = 10; 52.6%), catIV (n = 2; 10.5%), floR (n = 10; 52.6%), ermB (n = 14; 73.7%), tetO (n = 13; 68.4%), tetA (n = 9; 47.4%), mcr-4 (n = 8; 42.1%), and ampC (n = 2; 10.5%). Meanwhile, mcr-1, mcr-2, mcr-3, mcr-5, tet(X), tet(P), and tet(W) genes were not detected in all isolates. Class I and Class II integrons were detected in 92.3% (n = 24) and 65.4% (n = 17) isolates, respectively. About 31% (8 of the 26 isolates) isolates were carrying more than two resistance genes. According to our knowledge, this is the first study to detect class II integrons in Campylobacter spp. (C. jejuni). The high prevalence of cdtA, cdtB, cdtC, cadF, pldA, and ciaB genes and antibiotic resistance genes in C. jejuni in this study indicates the pathogenic potential of these isolates. Majority of the isolates demonstrated resistance to nalidixic acid, tetracycline (tet), and erythromycin (ermB), which are the drugs of choice for treating Campylobacter infections. Therefore, these findings highlight the importance of implementing an efficient strategy to control Campylobacter in chickens and to reduce antimicrobial use in the poultry industry, which will help to prevent the spread of infections to humans.